2022
DOI: 10.1002/adom.202102814
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Emission of Fluorescence and Room‐Temperature Phosphorescence for Ratiometric and Colorimetric Oxygen Sensing and Detection Based on Dispersion of Pure Organic Thianthrene Dimer in Polymer Host

Abstract: To improve room‐temperature phosphorescence (RTP) property, thianthrene (TA) is chemically modified into three intramolecular dimers (1TA1TA, 1TA2TA, and 2TA2TA) at different active sites. They all show dual‐emission of fluorescence and RTP after deoxygenation when they are dispersed in polymer matrix to form films. As for the RTP emission among their films, 2TA2TA shows the largest red shift peaking at 540 nm, the longest lifetime of 36.5 ms, and the highest RTP efficiency of 40.7%. These RTP characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 95 publications
0
21
0
Order By: Relevance
“…According to previous reports, phosphorescence materials can effectually eliminate the autofluorescence background and light scattering interference in the detection environment. 62,63 When monitoring the emission peak of 615 nm, the monoexponential decay lifetime of the 615 nm peak has been fitted as 261.80 μs (Fig. 2k and Table S2†).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, phosphorescence materials can effectually eliminate the autofluorescence background and light scattering interference in the detection environment. 62,63 When monitoring the emission peak of 615 nm, the monoexponential decay lifetime of the 615 nm peak has been fitted as 261.80 μs (Fig. 2k and Table S2†).…”
Section: Resultsmentioning
confidence: 99%
“…At last, a new mechanism of this kind of photo-oxidation reaction was put forward based on two main intermediates: the newly discovered quinoid oxidation-state radical and the well-known 1,2-dioxetane-like intermediate. Based on this mechanism, high-sensitivity oxygen sensing materials 20–23 can also be designed.…”
Section: Introductionmentioning
confidence: 99%
“…30–32 For instance, Liu et al fabricated a RTP polymer film for ratiometric and colorimetric sensing of O 2 . 33 Huang et al synthesized a series of flexible-crystalline RTP materials for optical flexible information storage. 34 Wang et al reported a RTP material with a photo-response, which exhibits the switchable photo-response response between UV and visible light.…”
Section: Introductionmentioning
confidence: 99%